The regulation and supervision of sukuk in global capital markets - Oseni, Umar Aimhanosi; Hassan, M. Kabir (Edward Elgar Publishing, 2014)
There is no doubt that the rate at which sukuk financing has been accepted in different jurisdictions outside the usual Muslim-majority countries is encouraging. This seemingly considerable feat comes with much responsibility and a proactive role for Shariah scholars and regulators. The chapter examines prevailing practices in the market and the need to enhance the Shariah compliance of the processes through proper regulation and follow-up supervision of sukuk transactions, particularly the underlying contracts. To this end, law and Shariah should complement each other with a view to ensuring compliance with the laid-down rules. A number of fundamental legal issues that are important in the ICM and consequently applicable to sukuk transactions have been raised. Some of these legal issues are either taken for granted during the drafting stage or assumed to be effective even though the philosophy underlying such issues differs from the original value proposition of Islamic economics. Therefore, it is incumbent on the stakeholders not only to promote a commercially viable industry but also to ensure that Shari‘ah principles are observed at all stages of sukuk transactions. This is where regulation and supervision intercept in the general framework of Islamic finance.